An investigation into the language of affect in the novel “nỗi buồn chiến tranh” by bảo ninh and in its translated version in the appraisal perspective - Trần,Huy Khánh (ĐHĐN., 2015)
The thesis aims to investigate and analyze the language of Affect in the category of Attitude, one of the three subsystems of the Appraisal theory in the novel ―Nỗi buồn chiến tranh‖ by Bảo Ninh and the English translational equivalents. In order to conduct the study, the descriptive analysis with the combination of both qualitative and quantitative research methods was adopted on the basis of the theories of functional grammar, appraisal and stylistics. The data were instances extracted from the novel ―Nỗi buồn chiến tranh‖ by Bảo Ninh and the equivalents in the English translational version by Phan Thanh Hao, Vo Bang Thanh, with Kateria A. Peirce. 577 Vietnamese samples of Affectual expressions and 519 English translational equivalents were collected in the novel in such grammatical forms as phrases, clauses and sentences. The thesis examined the semantic features and grammatical realizations of Affect expressions recognized in the novel in Vietnamese and the English equivalents. Semantically, the data were classified under the umbrella of appraisal theory and stylistic devices. In terms of functional grammar, the data were categorized into grammatical realizations of Affect. On the basis of the findings, some implications and suggestions on comprehending, translating the language of Affect as well as learning and teaching English through Affectual language in particular and Appraisal language in general were put forward.